Foot-in-the-door technique and reduction of driver's aggressiveness: A field study. (January 2016) - Guéguen, Nicolas; Martin, Angélique; Silone, Fabien; David, Mathieu
Highlights: The Foot-in-the-Door (FITD) technique was used to reduce driver's aggressiveness. Drivers were asked or not for a direction by a woman pedestrian. A confederate was instructed to block the traffic. Fewer drivers honked in the FITD condition and displayed their behavior later. Abstract: Research has reported that the foot-in-the-door technique is effective at increasing helping behavior. However, the effect of this technique on negative social behavior has never been examined. A field experiment was conducted to explore whether this technique could reduce aggressiveness. Drivers waiting at a traffic light were blocked by an experimental car. In the Foot-in-the-door condition, when the traffic light was red, a passerby confederate asked the driver for directions to a well-known store located in the area of the experiment. The confederate then thanked the driver and walked off in the direction indicated. In the control condition, no request was addressed to the car driver. When the traffic light turned green, the experimental car pretended to be blocked by an engine problem. The number of drivers who honked at the target car and the amount of time that elapsed before the drivers responded by honking their horns were the dependent variables. It was found that fewer drivers honked in the Foot-in-the-door condition and drivers who honked displayed their behavior later than those in the control condition. Self-perception theory was used to explain these results.